Exploring Shared SRAM Tables in FPGAs for Larger LUTs and Higher Degree of Sharing - Ali Asghar; Muhammad Mazher Iqbal; Waqar Ahmed; Mujahid Ali; Husain Parvez; Muhammad Rashid (International Journal of Reconfigurable Computing)
In modern SRAM based Field Programmable Gate Arrays, a Look-Up Table (LUT) is the principal constituent logic element which can realize every possible Boolean function. However, this flexibility of LUTs comes with a heavy area penalty. A part of this area overhead comes from the increased amount of configuration memory which rises exponentially as the LUT size increases. In this paper, we first present a detailed analysis of a previously proposed FPGA architecture which allows sharing of LUTs memory (SRAM) tables among NPN-equivalent functions, to reduce the area as well as the number of configuration bits. We then propose several methods to improve the existing architecture. A new clustering technique has been proposed which packs NPN-equivalent functions together inside a Configurable Logic Block (CLB). We also make use of a recently proposed high performance Boolean matching algorithm to perform NPN classification. To enhance area savings further, we evaluate the feasibility of more than two LUTs sharing the same SRAM table. Consequently, this work explores the SRAM table sharing approach for a range of LUT sizes (4–7), while varying the cluster sizes (4–16). Experimental results on MCNC benchmark circuits set show an overall area reduction of ~7% while maintaining the same critical path delay.